DENOTATION AND CONNOTATION IN LONDON’S WILLIAM BLAKE - Nuryadi, Nuryadi (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2021)
The industrial revolution had brought negative impact on society in England. The first is economic inequality and the second is the moral damage of society. The bad impact is described by William Blake in his poem entitled London. This study aims to find the description through the meaning of denotation and connotation. The poem was written in the era of romance. In this period, literary works were dominated by elements such as imagination, freedom of expression, and idealism. The research method is descriptive qualitative. This study uses a semantic approach, especially the meaning of denotation and connotation as well as the theory of English literature and culture. Based on the results of data analysis, five words with denotative and connotative meanings are found. Those words are chartered, manacles, blackning church, harlots and blasts. The connotative meanings of these five words are used to describe the economic inequality and the moral damage of society as a result of the industrial revolution. Roads and rivers are controlled by factories, freedom of speech is shackled, God's voice is no longer heard, women experience moral decadence and people live terrible fear because of the high crime rate.